2016
DOI: 10.5152/jtgga.2016.15214
|View full text |Cite
|
Sign up to set email alerts
|

Methods for endometrial preparation in frozen-thawed embryo transfer cycles

Abstract: Review 168 IntroductionFrozen-thawed (FT) embryo transfer is a procedure used for the storage and transfer of excess embryos obtained during in vitro fertilization (IVF)-intracytoplasmic sperm injection (ICSI) cycles. In recent years, improvements in laboratory conditions and limitations on the number of embryos to be transferred have led to a progressive increase in FT embryo transfer cycles. Another preferred practice to prevent multiple pregnancies in IVF cycles is to transfer a single embryo and freeze all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…For a successful implantation, a receptive endometrium and synchronization between the endometrium and the embryo are essential 6. To date, several methods of endometrial preparation have been attempted 7. Spontaneous ovulation is monitored in natural cycles.…”
mentioning
confidence: 99%
“…For a successful implantation, a receptive endometrium and synchronization between the endometrium and the embryo are essential 6. To date, several methods of endometrial preparation have been attempted 7. Spontaneous ovulation is monitored in natural cycles.…”
mentioning
confidence: 99%
“…One possible reason why RA‐RI in the early follicle phase was not predictive of pregnancy outcomes during the HRT cycle may be the effect of exogenously administered estrogen. The serum estradiol concentration averages around 100 pg/mL during the early to late follicular phase of the normal menstrual cycle, 48 whereas that exceeds 200 pg/mL with transdermal administration of estradiol during the HRT cycle 49,50 . In other words, an increase in endometrial blood flow would be expected due to higher estradiol levels in the HRT cycle than in the natural cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used different forms of GNRH-a and found no significant difference on the cycle outcome [23,18] . Kalem, et al [24] concluded that early luteinization may exist in 5% and complete down regulation with GNRH-a cannot be guaranteed in artificial cycles .The only detected positive factor affecting the pregnancy rate was the endometrial thickness which was determined by estrogen [25,26,27] .…”
Section: Discussionmentioning
confidence: 99%